Mutations in the glucocerebrosidase gene are common in patients with Parkinson's disease from Eastern Canada. (3rd May 2016) - Han, Fabin; Grimes, David A.; Li, Fang; Wang, Ting; Yu, Zhe; Song, Na; Wu, Shichao; Racacho, Lemuel; Bulman, Dennis E.
Abstract : Background : Mutations in the β -glucocerebrosidase gene ( GBA ) have been implicated as a risk factor for Parkinson's disease (PD). However, GBA mutations in PD patients of different ethnic origins were reported to be inconsistent. Methods : We sequenced all exons of the GBA gene in 225 PD patients and 110 control individuals from Eastern Canada. Result : Two novel GBA variants of c.-119 A/G and S(-35)N, five known GBA mutations of R120W, N370S, L444P, RecNciI and RecTL mutation (del55/D409H/RecNciI) as well as two non-pathological variants of E326K and T369M were identified from PD patients while only one mutation of S13L and two non-pathological variants of E326K and T369M were found in the control individuals. The frequency of GBA mutations within PD patients (4.4%) is 4.8 times higher than the 0.91% observed in control individuals ( X 2 = 2.91, p = 0.088; odds ratio = 4.835; 95% confidence interval = 2.524–9.123). The most common mutations of N370S and L444P accounted for 36.0% (9/25) of all the GBA mutations in this Eastern Canadian PD cohort. The frequency (6.67%) of E326K and T369M in PD patients is comparable to 7.27% in control individuals ( X 2 = 0.042, p = 0.8376), further supporting that these two variants have no pathological effects on PD. Phenotype analysis showed that no significant difference in family history, age at onset and cognitive impairment was identified between the GBA mutation carriers and non- GBA mutation carriers. Conclusion: GBA mutations were found to be a common genetic risk factor for PD in Eastern Canadian patients.